(نحو الإبداعية في إعداد البيئة اللغوية الفاعلة بإندونيسيا (تجارب المعاهد العصرية والنوادي العربية والجامعات - Rosyad, Sabil (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2018)
Quality upgrading needed in repairing Arabic learning, either in the system, curriculum, process and evaluation. One of the reconstruction efforts was to create language environment, because it is considered effective to increase language skills. The existence of Arabic environment becomes very important because always be present to surrounds and offers nuance of learning Arabic. Furthermore the language is a communal social product not an individual in person, till someone grow and absorb the language rules specified in their communities through learning or imitating. Therefore the creation of good language environment, true and conducive will have a big influence in mastering of Arabic language. Caused by the importance of language environment itself, the author discuss about theory of language acquisition and learning, some strategies for creating of conducive environment, procedure as well as media of language environment development, supporting and inhibiting factors.